Analisis Keterampilan Kerja Alumni SMK Tata Busana pada Industri Fashion di Malang - Yuyun Dwi Sayekti; Yoto Yoto; Widiyanti Widiyanti (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to analyze the employability skills possessed by alumni of vocational schools in Malang in facing the demands and needs of the fashion industry. Using a qualitative approach, this study focuses on the types of skills needed in the industry, the gap between the skills taught at school and those needed in the world of work, and employment opportunities for alumni in the fashion industry. This study used a qualitative approach to gain an in-depth understanding of the employability skills of SMK Cosmetology alumni and their relevance to the needs of the fashion industry in Malang. The research was conducted in three locations namely Samsuga, Yece, and Falasifa in Malang. The results showed that the fashion industry in Malang has a high demand for technical skills such as sewing and design, as well as interpersonal and entrepreneurial skills. The skills gaps found illustrate the need to improve the SMK curriculum to prepare more work-ready graduates. This research is expected to serve as a guide for vocational education institutions, especially in adjusting the curriculum to the needs of the fashion industry.